2011
DOI: 10.1590/s1806-66902011000100007
|View full text |Cite
|
Sign up to set email alerts
|

Manejo de irrigação e nitrogênio no feijoeiro comum cultivado em sistema plantio direto

Abstract: Resumo -Diante de inovações tecnológicas, como a irrigação, o feijoeiro vem sendo cultivado por produtores que dispõem dos mais variados níveis de tecnologia que, em épocas adequadas, permitem que o plantio tenha melhoria na produtividade. O objetivo deste trabalho foi avaliar diferentes manejos de irrigação e doses de nitrogênio em feijoeiro-comum cultivado em sistema plantio direto no município de Aquidauana -MS. O experimento foi realizado na Unidade Universitária de Aquidauana -Universidade Estadual do Mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
1
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 8 publications
0
11
1
6
Order By: Relevance
“…SANTANA et al (2008) found that the cultivar BRSMG Talismã when subjected to the water depths considered deficient as well as excessive, reduced most of its evaluated variables. LOPES et al (2011) evaluated the productivity of bean crop under different methods of irrigation management, verified that the highest yields were 3031.11 kg ha -1 and 3005.02 kg ha -1 with management performed by Class A pan and Hargreaves-Samani equation (to obtain the reference evapotranspiration). FARINELLE & LEMOS (2010) found an average yield of 4157 kg ha -1 and 4564 kg ha -1 of growing bean in the dry season in two years of production, when evaluating different genotypes in the city of Botucatu, SP.…”
Section: Resultsmentioning
confidence: 88%
See 2 more Smart Citations
“…SANTANA et al (2008) found that the cultivar BRSMG Talismã when subjected to the water depths considered deficient as well as excessive, reduced most of its evaluated variables. LOPES et al (2011) evaluated the productivity of bean crop under different methods of irrigation management, verified that the highest yields were 3031.11 kg ha -1 and 3005.02 kg ha -1 with management performed by Class A pan and Hargreaves-Samani equation (to obtain the reference evapotranspiration). FARINELLE & LEMOS (2010) found an average yield of 4157 kg ha -1 and 4564 kg ha -1 of growing bean in the dry season in two years of production, when evaluating different genotypes in the city of Botucatu, SP.…”
Section: Resultsmentioning
confidence: 88%
“…LOPES et al (2011) observed that the number of seeds per pod was greater when irrigation management was carried out by tensiometry (3.93) and by . SANTANA et al (2008) observed that there was no influence of the time of irrigation suspension and the applied water depths in the number of grains per plant and number of seeds per pod.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Conforme colocado por Doorenbos & Kassam (1994) e em razão do curto período do ciclo do feijoeiro, pequenos períodos de deficiência hídrica podem afetá-lo severamente. Os resultados obtidos se assemelham aos de Pavani et al (2008) e Lopes et al (2011); esses autores também observaram maiores produtividades no feijoeiro irrigado manejado com base na evapotranspiração estimada pelo método do tanque Classe A em comparação com manejo por tensiometria; apesar disto, resultados diferentes foram obtidos por Lopes et al (2004), que compararam o desempenho dos métodos da tensiometria, balanço hídrico e tanque e obtiveram economia de 15% na água de irrigação aplicada com manejo por tensiometria, sem afetar a produtividade de grãos do feijoeiro. Tabela 2.…”
Section: Methodsunclassified
“…O tanque pode ser instalado no campo, próximo à cultura. Normalmente, apresenta valores superestimados da evapotranspiração com incrementos significativos na produtividade do feijoeiro (Pavani et al, 2008;Lopes et al, 2011).…”
Section: Introductionunclassified